ISLAMIC REGULATIONS AND ISLAMIC BANK MARGINS: AN EMPIRICAL INVESTIGATION INTO ASEAN COUNTRIES - Fatin Nur Hidayah Taib Khan; Nurhafiza Abdul Kader Malim; Tajul Ariffin Masron (Journal of Islamic Monetary Economics and Finance, 2021)
This paper examines the impact of Islamic regulations on Islamic bank margins in ASEAN countries, utilising the fixed-effect method. The sample consists of 27 Islamic banks in Malaysia, Indonesia, Singapore and Thailand covering the period 2009 to 2017. The results suggest that Islamic regulations, such as the Islamic regulatory framework and Shari’ah supervisory board, are negatively associated with Islamic bank margins. These results have important policy implications for regulators, indicating that they should impose a separate regulatory framework for Islamic banks and bank managers to increase the number of Shari’ah scholars on the Shari’ah board in lowering Islamic bank margins. Overall, the findings suggest that Islamic banks should adopt regulations that should follow Shari’ah requirements, as they help to lower the cost of financial intermediation. As for the other control variables, only the Lerner index has a positive and significant impact on ASEAN Islamic bank's margin. Therefore, appropriate policies are necessary to foster competition in Islamic banks.